FACTORS INFLUENCING WILLINGNESS TO COMMUNICATE IN A COMMUNITY COLLEGE ESL CLASSROOM - Wirdawati Ahmad @ Mohd Isa; Muhammad Fairuz Jamil; Siti Nurhazirah Lidon (Journal of Islamic, Social, Economics and Development, 2022)
The purpose of this research is to investigate the situational factors that influence Malaysian community college students’ willingness to communicate (WTC). A quantitative research design was adopted to obtain data from 53 respondents in three different academic courses’ answers to the questionnaire. The analysis of the data using SPSS for the mean of frequency shows that the participants were moderate in WTC levels and that teachers, peers, topic preferences, types of activities, and seating location are the factors influencing WTC. Therefore, a variety of variables influence students' WTC and avoid assuming that someone's WTC is influenced only by one factor.